2011
DOI: 10.1001/archoto.2010.227
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Children Diagnosed as Having Coagulopathies Following Posttonsillectomy Bleeding

Abstract: In children presenting with PTB, activated partial thromboplastin time and PFA studies and hematology consultations are helpful in identifying occult coagulopathies. The definition of PTB should be broadened to include children with any history of oral bleeding, regardless of examination findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The goal in both adult and pediatric cases is better life quality. [1][2][3][4][5][6][7] Complications of surgery in this situation are pain, feeling nauseous or actual vomiting, fluid loss and hemorrhage. [8,9] Post-tonsillectomy hemorrhage (PTH) numbers amongst the gravest consequences of tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The goal in both adult and pediatric cases is better life quality. [1][2][3][4][5][6][7] Complications of surgery in this situation are pain, feeling nauseous or actual vomiting, fluid loss and hemorrhage. [8,9] Post-tonsillectomy hemorrhage (PTH) numbers amongst the gravest consequences of tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that children should have aPTT and PFA testing as part of their initial workup and referrals to hematology after PTH were useful. 18 Conversely, a series of 93 secondary hemorrhages could not identify any significant clotting abnormalities and suggested that such testing should not be undertaken routinely unless clinical suspicion is warranted. 19 Consequently, many clinicians consider PT or aPTT to be relatively insensitive to detect vWD or hemophilia with poor cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous review, children presenting with PTH had significant differences in aPTT and platelet function assay (PFA). The authors concluded that children should have aPTT and PFA testing as part of their initial workup and referrals to hematology after PTH were useful 18 . Conversely, a series of 93 secondary hemorrhages could not identify any significant clotting abnormalities and suggested that such testing should not be undertaken routinely unless clinical suspicion is warranted 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conclude that patients with diagnosed BDs do not have an increased risk of PTB, and some suggest that appropriate pre‐surgical treatment mitigates PTB's risk. 10 , 11 , 12 Others indicate that the risk of secondary PTB, defined by PTB after the first 24 postoperative hours, increases in this subset of patients with PTB rates around 8.7%‐15.5%. 9 , 13 , 14 Although more research is needed to determine the true risk of PTB in patients with BDs, it is still imperative for children undergoing T/A procedures to obtain pretreatment medications to prevent potentially life‐threatening bleeds.…”
Section: Introductionmentioning
confidence: 99%
“…PTB in patients with BDs is a controversial topic in the current literature. Some studies conclude that patients with diagnosed BDs do not have an increased risk of PTB, and some suggest that appropriate pre‐surgical treatment mitigates PTB's risk 10‐12 . Others indicate that the risk of secondary PTB, defined by PTB after the first 24 postoperative hours, increases in this subset of patients with PTB rates around 8.7%‐15.5% 9,13,14 .…”
Section: Introductionmentioning
confidence: 99%